Cocaine and acute renal failure - Terribile, M.; Paracuollo, D.; D’Anna, F.; Genualdo, R.; Rossano, R.; Terribile, M.; Paracuollo, M.; Capuano, M. (Giornale di Clinica Nefrologica e Dialisi, 2018)
No abstract